Sex-related and performance differences in contractile properties, ROM, strength, and dynamometry performance of world-class flatwater canoeists - Álvarez-Yates, T.; Cuba-Dorado, A.; Iglesias-Caamaño, M.; Serrano-Gómez, V.; Nakamura, F. Y.; García-García, O. (Applied Sciences, 2024)
The inclusion of women canoe in the Olympic Games reflects the growth and development that women have ahead of them in this modality. Therefore, the aim of this study was to explore sex and performance level differences in muscle contractile properties through Tensiomyography (TMG), range of motion (ROM), strength, and canoe-specific functional electromechanical dynamometry (FEMD) performance and establish performance differences between international medalists and non-medalists. Twelve male and nine female canoeists from the Spanish and Portuguese national canoe teams were assessed through TMG, ROM, strength, and canoe-specific isometric and incremental FEMD tests. Few sex and performance level differences were found in TMG and ROM; however, significant sex differences were found in the strength and FEMD tests. Male canoeists had a greater Fmax in Leg Press, Pm and Pmax in canoe position cable row, 1RM bench press and bench pull, Fm and Fpeak canoe-specific isometric FEMD test and number of strokes, and Fpeak and Pmax on the incremental FEMD test than females. International medalists showed a lower time until reaching Vmax and Pmax in Leg Press on both sides and a greater number of strokes and Fpeak in the maximal incremental FEMD test than non-medalists. This study reinforces the utility of the use of TMG and FEMD for assessing and monitoring world-class athletes.